(untitled) (Veterinary Science, 2022)
Previous studies determined that the oral administration of hydroalcoholic extracts obtained from the aerial parts of Equisetum giganteum L. n.v. cola de caballo, Cortaderia selloana (Schult & Schultz. f.) n.v. cortadera, Anthemis cotula L. n.v. manzanilla amarga y Atriplex undulata D. Dietr. n.v. zampa blanca prevent gastric ulcers induced by hypothermia and immobilization in mice. The formation of gastric ulcers in this experimental model is caused by a decrease in cytoprotective factors and by a mechanical erosive effect produced in the mucosa by increased gastric motility. In order to determine whether these extracts produce a decrease in gastric motility, in this study gastric emptying of a radiopaque substance was observed by taking radiographs at 0, 60, 100 and 160 minutes after the start of the test. A delay in gastric emptying time with respect to the control group animals was interpreted as a decrease in motility. The results of this work allow us to conclude that all the extracts of Atriplex undulata, Equisetum giganteum, Cortaderia Selloana and Anthemis cotula show an inhibitory effect on gastric motility from higher to lower respectively